Effect of parenting competence on postpartum depression: The role of ruminative thinking - Zheng, Shiyu; Nor Mazlina, Ghazali; Voon, Siok Ping; Shen, Jilin (Malque Publishing, 2024)
Postpartum depression (PPD) has a high prevalence worldwide and adversely impacts both family and society. This study focuses on the association between parenting competence (PC), ruminative thinking (RT), and PPD among postpartum women, specifically examining the mediating role of RT. This quantitative study employed structural equation modeling and collected data using purposive sampling. Based on previous evidence,three-factor models require a minimum sample size of 86, though most studies recommend a value exceeding 200. After excluding missing data and outliers, the final sample consisted of 269 women, all within eight weeks postpartum, from three hospitals in China.The inclusion criteria were having at least a middle school diploma, voluntary participation, and no recent history of psychotherapy and medication treatment. The instruments used were the Edinburgh Depression Scale, Parenting Sense of Competence Scale, and Rumination Response Scale. The study sequentially performed descriptive statistics, tested measurement models and structural models, and calculated path coefficients. The results indicated that (i) PC negatively predicted PPD; (ii) PC negatively predicted RT; and (iii) RT positively predicted PPD. Furthermore, RT mediated the relationship between PC and PPD, with PC and RT exerting nearly equivalent effects on PPD. The study confirmed the impact of PC on PPD through RT among Chinese postpartum women. Both PC and RT are critical factors in PPD. The study establishes a structural framework for understanding the relationships between PC, PPD, and RT, emphasizing the significant roles of PC and RT in the development of PPD. This provides valuable insights into understanding the mechanisms of PPD and offering reference for future research. In practice,healthcare professionals and family members should consider these factors, particularly ruminative thinking. By improving treatment plans and care strategies, they can reduce the incidence of postpartum depression and enhance the quality of life for postpartum women.